Islamic Spiritual Capital Implementation at BMT UGT Sidogiri - Kurniasari, Widita; Sawarjuwono, Tjiptohadi; Ryandono, Muhamad Nafik Hadi (Economica: Jurnal Ekonomi Islam, 2019)
Abstract: The purpose of this study was to obtain an in-depth description of the implementation of the concept of Islamic Spiritual Capital at BMT UGT Sidogiri. The approach used in this research is Islamic phenomenology. This research explores events/phenomena and organizational culture at BMT UGT Sidogiri. This method helps to reveal how to implement Islamic Spiritual Capital in the culture of working at BMT UGT Sidogiri. The results showed that the importance of civilize Islamic Spiritual Capital was reflected through prayer discipline, time discipline and rule discipline. Uphold the work ethic of three -as in working, they are working hard, working smart and working sincerely. This work ethic involves the body, brain and heart. Islamic leadership is basically a belief that prioritizes the attributes of the STAFF (Siddiq, Tabligh, Amanah, Fathonah). Motivation in working is intended to worship, seek the blessing of Allah and become a charity hereafter so that the goal is not only for the world. So that, every employee has an Islamic commitment that is having the confidence to be loyal to the organization and istiqomah (steadfastness) at work.Abstrak: Tujuan dari penelitian ini adalah untuk memperoleh gambaran yang mendalam tentang implementasi konsep Modal Spiritual Islam di BMT UGT Sidogiri. Pendekatan yang digunakan dalam penelitian ini adalah fenomenologi Islam. Penelitian ini mengeksplorasi peristiwa/fenomena dan budaya organisasi di BMT UGT Sidogiri. Cara ini membantu mengungkap bagaimana mengimplementasikan Modal Spiritual Islam dalam budaya kerja di BMT UGT Sidogiri. Hasil penelitian menunjukkan bahwa pentingnya modal kerohanian Islam yang beradab tercermin melalui disiplin shalat, disiplin waktu dan disiplin aturan. Menjunjung tinggi etos kerja tiga -sebagai dalam bekerja, mereka bekerja keras, bekerja cerdas dan bekerja dengan ikhlas. Etos kerja ini melibatkan tubuh, otak dan hati. Kepemimpinan Islam pada dasarnya adalah keyakinan yang mengutamakan atribut STAF (Siddiq, Tabligh, Amanah, Fathonah). Motivasi dalam bekerja dimaksudkan untuk beribadah, mencari ridho Allah dan menjadi sedekah akhirat agar tujuannya tidak hanya untuk dunia. Sehingga setiap karyawan memiliki komitmen islami yaitu memiliki kepercayaan diri untuk setia pada organisasi dan istiqomah (ketabahan) dalam bekerja.